2006
DOI: 10.1212/01.wnl.0000240225.04000.1a
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of duloxetine in diabetic peripheral neuropathic pain

Abstract: This study confirms previous findings that duloxetine at 60 mg QD and 60 mg BID is effective and safe in the management of diabetic peripheral neuropathic pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
284
1
20

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 445 publications
(329 citation statements)
references
References 34 publications
21
284
1
20
Order By: Relevance
“…Doses of 60 and 120 mg/day showed efficacy in the treatment of pain associated with DSPN in multicenter randomized trials, although some of these had a rather high drop-out rate (15, 86,94,96,[98][99][100][101]. Duloxetine was also suggested to induce improvement in neuropathy-related quality of life (100).…”
Section: Approved Medicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Doses of 60 and 120 mg/day showed efficacy in the treatment of pain associated with DSPN in multicenter randomized trials, although some of these had a rather high drop-out rate (15, 86,94,96,[98][99][100][101]. Duloxetine was also suggested to induce improvement in neuropathy-related quality of life (100).…”
Section: Approved Medicationsmentioning
confidence: 99%
“…Both venlafaxine and duloxetine (see above) inhibit the reuptake of serotonin and norepinephrine without the muscarinic, histaminic, and adrenergic side effects that accompany the use of the tricyclic agents (98)(99)(100)102). However, the level of evidence for pain reduction associated with DSPN is higher with duloxetine (see above).…”
Section: Monoamine Reuptake Inhibitorsmentioning
confidence: 99%
“…The literature regarding SNRI use for the prevention of chronic post-surgical pain is limited; however, given that the SNRI medication (duloxetine) is a firstline medication for the treatment of chronic neuropathic pain [67], its role in the prevention of chronic post-surgical pain should be further investigated. Duloxetine has been shown to be efficacious for the treatment of diabetic peripheral neuropathy and fibromyalgia [68][69][70][71]. Appropriately powered trials are necessary to examine the efficacy of the SNRIs in CPSP prevention, including dose-response studies and head-to-head comparisons with other drugs, such as pregabalin.…”
Section: Selective Norepinephrine and Serotonin Re-uptake Inhibitors mentioning
confidence: 99%
“…Duloxetine has been approved for the pain associated with diabetic peripheral neuropathy (DPN), based on the positive results of clinical trials [12][13][14]. However two recent studies Yang et al 2013), used duloxetine in CIPN and they found significant reduction in pain scores in duloxetine group than the placebo [15,16].…”
Section: Discussionmentioning
confidence: 99%